Gambaran Harga Diri Orang dengan HIV/AIDS (ODHA) di Violet Community Yogyakarta Tahun 2008 - Pramesti, Despita (STIKES 'Aisyiyah Yogyakarta, 2008)
The issues which caused stress to ‘ODHA’ are the high level of death rate resulted by this disease and mainly the public perspective on ‘Orang Dengan HIV/AIDS (ODHA)’ that consequently influence their self-esteem. To observe the self-esteem within ‘Orang Dengan HIV/AIDS (ODHA)’ and the factors influencing the self-esteem within ‘Orang Dengan HIV/AIDS (ODHA)’ in violet community Yogyakarta. This is a non experimental research using descriptive explorative research planning with qualitative method. Sampling used in this research is non probabilistic or purposive sampling. This research shows that observation on ‘Orang Dengan HIV/AIDS (ODHA)’ regarding with their self-esteem in violet community Yogyakarta based on the criteria of acceptance, respected and competence on 5 respondence would lead to the result of high assessment of self-esteem among them. And on the criteria sense of value 1 respondence would lead to the result of high assessment of self-esteem and 4 respondence would lead to the result of low assessment of self-esteem. Factors which influenced the selfesteem on ‘Orang Dengan HIV/AIDS (ODHA)’ in Violet community were the acceptance of other individual on their condition and also their strength and weakness, success, appreciation from others, support from other HIV/AIDS carrier and support from friends in the community. Overlook the strength and weakness of ‘Orang Dengan HIV/AIDS (ODHA)’, there by we can develop more so that ‘Orang Dengan HIV/AIDS (ODHA)’ we bigger self-esteem then feel more valuable.